2015
DOI: 10.1371/journal.pmed.1001855
|View full text |Cite
|
Sign up to set email alerts
|

Individual Participant Data (IPD) Meta-analyses of Randomised Controlled Trials: Guidance on Their Use

Abstract: Jayne Tierney and colleagues offer guidance on how to spot a well-designed and well-conducted individual participant data meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
288
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(301 citation statements)
references
References 61 publications
2
288
1
Order By: Relevance
“…For example, Debray et al found that erythema was a statistically significant predictor of deep vein thrombosis (DVT) in a one‐stage analysis ( p  = 0.03), but not a two‐stage analysis ( p  = 0.12) 3. For this reason, Tierney et al advise, ‘It is important, therefore, that the choice of one or two‐stage analysis is specified in advance or that results for both approaches are reported’ 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Debray et al found that erythema was a statistically significant predictor of deep vein thrombosis (DVT) in a one‐stage analysis ( p  = 0.03), but not a two‐stage analysis ( p  = 0.12) 3. For this reason, Tierney et al advise, ‘It is important, therefore, that the choice of one or two‐stage analysis is specified in advance or that results for both approaches are reported’ 13.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate this, Tierney et al give a binary outcome example where the effects of anti‐platelets on pre‐eclampsia in pregnancy from two‐stage (relative risk = 0.90, 95% CI = 0.83 to 0.96) and one‐stage (relative risk = 0.90, 95% CI = 0.83 to 0.97) analyses were almost identical 2, 13.…”
Section: An Introduction To One‐stage and Two‐stage Ipd Meta‐analysismentioning
confidence: 99%
“…Studies investigating moderators of the exercise intervention effects on physical fitness are scarce, and single RCTs are generally underpowered to investigate such moderator effects. The use of IPD from multiple RCTs allows testing of moderators with interaction tests in larger samples 30. Therefore, we aimed to identify demographic, clinical, intervention-related and exercise-related moderators of the exercise intervention effect on UBMS, LBMS, LBMF and aerobic fitness using IPD available in the POLARIS database 29…”
Section: Introductionmentioning
confidence: 99%
“…17 Our output complied with the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) reporting guidelines for IPD meta-analysis. 18 …”
mentioning
confidence: 99%